Building new plants or entering by acquisition? Estimation of an entry model for the U.S. cement industry - Hector Perez-Saiz (Bank of Canada, 2011)
In many industries, firms usually have two choices when expanding into new markets: They can either build a new plant (greenfield entry) or they can acquire an existing incumbent. In the U.S. cement industry, the comparative advantage (e.g., TFP or size) of entrants versus incumbents and regulatory entry barriers are important factors that determine the means of expansion. Using a rich database of the U.S. Census of Manufactures (1963-2002), an entry game is proposed to model this decision and estimate the supply and demand primitives to determine the importance of these factors. Two policies that affect the entry behavior and industry equilibrium are considered: An asymmetric environmental policy that creates barriers to greenfield entry and a policy that creates barriers to entry by acquisition. In the counterfactual analysis it is found that a less favorable environment for acquisitions during the Reagan-Bush administration would decrease the acquired plants by 90% and increase greenfield entry by 21%. Also, the Clean Air Act Amendments of 1990 increased the number of acquisitions by 3.5%. Furthermore, my simulations suggest that regulations that create barriers to greenfield entry are less favorable in terms of welfare than regulations that create barriers to entry by acquisition. Finally, it is shown how the parameter estimates change with the traditional approach in the entry literature where entry by acquisition is not considered, and when using a simple OLS estimation.
Keywords: L13; L40; L61; 330; Productivity; Market structure and pricing; Econometric and statistical methods; Strategisches Management; Markteintritt; Direktinvestition; Unternehmensgründung; Übernahme; Marktstruktur; Produktivität; USA